What has the National Cancer Database taught us about oral cavity squamous cell carcinoma?. Issue 1 (January 2022) - Graillon, N.; Iocca, O.; Carey, R.M.; Benjamin, K.; Cannady, S.B.; Hartner, L.; Newman, J.G.; Rajasekaran, K.; Brant, J.A.; Shanti, R.M.
Abstract: The wealth of data in the National Cancer Database (NCDB) has allowed numerous studies investigating patient, disease, and treatment-related factors in oral cavity squamous cell carcinoma (OCSCC); however, to date, no summation of these studies has been performed. The aim of this study was to provide a concise review of the NCDB studies on OCSCC, with the hopes of providing a framework for future, novel studies aimed at enhancing our understanding of clinical parameters related to OCSCC. Two databases were searched, and 27 studies published between 2002 and 2020 were included. The average sample size was 13, 776 patients (range 356–50, 896 patients). Four areas of research focus were identified: demographic and socioeconomic status, diagnosis, prognosis, and treatment. This review highlights the impact of age, sex, ethnicity, and socioeconomic status on the prognosis and management of OCSCC, describes the prognostic factors, and details the modalities and indications for neck dissection and adjuvant therapy in OCSCC. In conclusion, the NCDB is a very valuable resource for clinicians and researchers involved in the management of OCSCC, offering an incomparable perspective on a large dataset of patients. Future developments regarding hospital information management, review of data accuracy and completeness, and wider accessibility will help clinicians to improve the care of patients affected by OCSCC.